The role and impact on quality of exogenous and endogenous lipids during sponge cake making. (August 2021) - Pycarelle, Sarah C.; Delcour, Jan A.
Abstract: Background: Sponge cakes (SCs) are made from wheat flour, sugar, eggs, leavening agents and optionally exogenous lipid additives (e.g. monoacylglycerols). Such additives facilitate aeration during batter mixing, provide gas cell stability after mixing and facilitate the production of high-quality cakes. However, in reply to consumer demands, industry is looking for alternatives for the use of such additives. This search requires a fundamental understanding of (i) ingredient functionality during SC (a foam-type cake) making in general and of (ii) the functionality of endogenous lipids that may serve as clean label alternatives in particular. Scope and approach: The entire SC making process (i.e. mixing, early and late baking and cooling) is discussed and key phenomena are identified. Furthermore, the role of endogenous and exogenous lipids and their relation to SC quality are described in detail. Finally, take home messages and prospects for further research are put forward. Key findings and conclusions: Use of exogenous lipids leads to high-quality SCs because they impact air-liquid interface stability but also timing and extent of cake structure setting during baking. Their use increases air incorporation during mixing and cake matrix stiffness during late baking. When preparing SCs without using exogenous lipids, flour and egg lipids determine cake quality by their impact at the air-liquid interface in batter. Although both proteins and lipids adsorb at the interface, proteins have a more prominent role. In contrast to egg yolk lipids, free flour lipids lower air-liquid interface stability. Highlights: Air-liquid interface stability is crucial in sponge cake (a foam-type cake) making. In sponge cake batter, flour and egg lipids impact air-liquid interface stability. Exogenous lipid additives increase matrix stiffness during baking. Timing of leavening and structure setting need to match to obtain high-quality cake.